William Lethaby, symbolism and the occult - Sangha, Amandeep K. (2017)
The thesis will reconsider the thought and design work of the architect William Richard Lethaby (1857–1931). The research will focus upon Lethaby’s affiliation with the occult, with particular reference to alchemy. The relationship between nineteenth- and twentieth-century architects and occultism has been overlooked, and in many cases intentionally neglected, by scholars and historians. Current scholarship in the field has placed a greater emphasis on twentieth-century proponents of the occult. This detailed study on Lethaby and the occult therefore forms an original contribution to existing scholarship, highlighting the parallels between the nineteenth-century architect’s work and the ideology and imagery of the occult. The thesis will demonstrate Lethaby’s familiarity with occult concepts and the extent to which these were employed by him in his work. The study will then go on to examine how Lethaby’s fascination with occult themes and magic had a consequent influence on his contemporaries and question how far this interest in the occult impacted the future generation of designers and subsequent movements.